How top managers’ sport experience exploits environmental proactivity in state-owned enterprises. - Zhang, Jing; Pan, Pengyuan; Pan, Jianhua; Feng, Yuan (Frontiers in Environmental Science, 2022)
Combining the perspectives of upper echelon theory and institution theory, we investigate how top managers’ sport experience exploits corporate environmental proactivity in China, and embed this question into state ownership. With the sample of Chinese listing enterprises from 2008 to 2018, we find that both sport experience and state ownership positively promote corporate environmental proactivity, while state ownership crowds out the promotion of top managers’ sport experience. Further analyses show that position and financial experience of top manager as well as corporate investing efficiency and location matter in these processes. Thus, we extend the understanding of how top managers’ sport experience and state ownership interact and influence corporate environmental proactivity. We therefore provide new instruments to promote corporate environmental proactivity, and respectively extend upper echelon theory from the perspective of top managers’ sport experience as well as institution theory from the perspective of state ownership.